A ilha de Hainan sujeita a Cantão e o distrito de Chão-Hing a Macau. (1901)
This 1901 diplomatic correspondence, originating from the Portuguese Ministry of Foreign Affairs’ General Directorate of Political and Diplomatic Affairs, concerns ecclesiastical jurisdictional negotiations between Portugal and France regarding territories in China. Dated 16 February 1901 and addressed to a high-ranking official, the document records an agreement reached between the Portuguese and French governments on the reassignment of ecclesiastical authority over Hainan Island, previously under the Diocese of Canton prior to the 1876 arrangement between the Vicar General of Macau and the Apostolic Prefect. The agreement stipulates that, in exchange for returning Hainan to the Diocese of Canton, the Bishop of Macau would gain jurisdiction over the Chao-Shing district adjacent to Shean-Chau, where he already exercised ecclesiastical authority. Two key conditions are noted: the necessity of initiating territorial demarcation procedures pending formal approval by the Holy See, and the provisional nature (provisoria tantum ratione) of the jurisdictional transfer. The French Legation in Lisbon communicated its government’s assent to these terms on 20 December 1900 and again on 13 February 1901. The document further references a communication from the Apostolic Nuncio dated 6 October 1900, conveying the Holy See’s requirement for formal ratification and canonical title before final confirmation. This file, part of Section No. 2, File 51, reflects the intersection of colonial diplomacy, Catholic ecclesiastical administration, and international agreements at the turn of the twentieth century.
Keywords: Agreement Terms; Apostolic Prefect; Bishop of Macau; Chao-King district; Colonial Church Administration; Diocese of Canton; Diplomatic Accord; Diplomatic Correspondence; Ecclesiastical Authority Transfer; Formal Documentation; French Legation in Lisbon; General Directorate Political Diplomatic Affairs; Hainan Island; Historical Archive; Holy See approval; Jurisdictional Negotiation; Portuguese Ministry of Foreign Affairs; Portuguese-French ecclesiastical jurisdiction; Previous 1876 Arrangement; Provisoria Tantum Ratione; Religious-Diplomatic Law Intersection; Shean-Chau; Sino-Portuguese Relations; Territorial Demarcation; Transcription; Vicar General of Macau